EFEK PEMBERIAN ANABOLIK ANDROGENIK STEROID INJEKSI DOSIS RENDAH DAN TINGGI TERHADAP GAMBARAN MORFOLOGI TESTIS WISTAR (Rattus novergicus) - Wongkar, Jimmy (e-Biomedik, 2014)
AbstractBackground: Anabolic androgenic steroids (AAS) are synthetic derivatives of endogenous male sex hormone testosterone, which stimulate protein synthesis and masculinization process. The use of AAS without indication can cause negative side effects on the reproductive system, especially in men. Androgenic anabolic steroids may interfere with the regulation of testosterone and gonadotropin hormone that may lead to sexual dysfunction, infertility (disruption of spermatogenesis) and testicular atrophy.Objective: To determine the morphology of wistar testes, treated with anabolic androgenic steroids injection at a low and high doses.Methods: Research subjects were 21 wistar rats divided into 7 groups. Group A were treated with standard pellets for 56 days (negative control), termination on day 29, 43, 57. Group B treated with low dose of AAS anabolic treatment and standard pellets for 28 days, termination on the 29th day. Group C treated with low dose of AAS anabolic treatment and standard pellets for 42 days, termination on the 43rd day . Group D treated with AAS injection on low dose and standard pellets for 56 days, termination on the 57th day. Group E treated with AAS injection on a high dose and standard pellets for 28 days, termination on the 29th day. Group F treated with AAS injection on a high dose and standard pellets for 42 days, termination on the 43rd day. Group G was given high-dose injection AAS treatment and standard pellets for 56 days, termination on the 57th day.Results: Group A showed normal testicular morphology and spermatogenesis. Group B showed disruption of spermatogenesis but testicular atrophy did not occur. Groups C and D showed disruption of spermatogenesis and testicular atrophy. Group E showed disruption of spermatogenesis but testicular atrophy did not occur. Group F and G showed an improvement on spermatogenesis and testicular atrophy did not occur.Conclusions: Administration of low doses of anabolic androgenic steroids injection caused morphological change in rat’s testes manifested as atrophy in 4 weeks, while after administration of high doses anabolic androgenic steroids injection also caused morphological change in rat’s testesin the form of fewer interstitial cell compared to negative control. However administration for longer than 6 weeks does not cause athropy. The effects of AAS on various other organs were not tested in this study.Keywords: Anabolic androgenic steroids, atrophy, testicular.Abstrak:Latar Belakang: Anabolik androgenik steroid (AAS) adalah derivat sintesis dari hormon sex testosteron endogen pria yang merangsang proses sintesis protein dan maskulinisasi. Penggunaan AAS tanpa indikasi memberikan efek samping yang buruk pada sistem reproduksi terutama pada pria. Anabolik androgenik steroid dapat mengganggu regulasi hormon testosteron dan gonadotropin sehingga dapat menyebabkan terjadinya disfungsi seksual, infertilitas (terganggunya spermatogenesis) dan atrofi testis.Tujuan: Untuk mengetahui gambaran morfologi testis wistar yang diberikan anabolik androgenik steroid (AAS) injeksi dosis rendah dan dosis tinggi.Metode: Subjek penelitian berupa 21 ekor wistar yang dibagi menjadi 7 kelompok. Kelompok A diberi pelet standar selama 56 hari (kontrol negatif), terminasi pada hari ke-29, 43, 57. Kelompok B diberi perlakuan AAS injeksi dosis rendah dan pelet standar selama 28 hari, terminasi hari ke-29. Kelompok C diberi perlakuan AAS injeksi dosis rendah dan pelet standar selama 42 hari, terminasi hari ke-43. Kelompok D diberi perlakuan AAS injeksi dosis rendah dan pelet standar selama 56 hari, terminasi hari ke-57. Kelompok E diberi perlakuan AAS injeksi dosis tinggi dan pelet standar selama 28 hari, terminasi hari ke 29. Kelompok F diberi perlakuan AAS injeksi dosis tinggi dan pelet standar selama 42 hari, terminasi hari ke-43. Kelompok G diberi perlakuan AAS injeksi dosis tinggi dan pelet standar selama 56 hari, terminasi hari ke-57.Hasil: Pada kelompok A didapatkan gambaran morfologi testis dan proses spermatogenesis yang normal. Pada kelompok B didapatkan gambaran proses spermatogenesis yang terganggu namun belum terjadi atrofi testis. Pada kelompok C dan D didapatkan gambaran proses spermatogenesis yang terganggu dan testis yang mengalami atrofi. Pada kelompok E didapatkan gangguan proses spermatogenesis namun tidak terjadi atrofi testis. Pada kelompok F dan G didapatkan gambaran perbaikan proses spermatogenesis dan tidak terjadi atrofi testis.Kesimpulan: pemberian anabolik androgenik steroid injeksi dosis rendah pada wistar menyebabkan perubahan gambaran morfologi testis berupa atrofi bila diberikan lebih dari 4 minggu, sedangkan pemberian anabolik androgenik steroid injeksi dosis tinggi menyebabkan penurunan kepadatan sel intertisial tetapi tidak menyebabkan atrofi pada testis bila diberikan lebih dari 6 minggu. Efek AAS terhadap berbagai organ lain tidak diteliti dalam penelitian ini.Kata Kunci: Anabolik androgenik steroid, atrofi , testis.